Sediment sources and connectivity linked to hydrologic pathways and geomorphic processes: a conceptual model to specify sediment sources and pathways through space and time - Cho, Se Jong; Karwan, Diana L.; Skalak, Katherine; Pizzuto, James; Huffman, Max E. (Frontiers in Water, 2023)
Sediment connectivity is a conceptualization for transfer and storage of sediment among different geomorphic compartments across upland landscapes and channel networks. Sediment connectivity and dysconnectivity are linked to the water cycle and hydrologic systems with the associated multiscale interactions with climate, soil, topography, ecology, and landuse/landcover under natural variability and human intervention. We review current sediment connectivity and modeling approaches evaluating and quantifying water and sediment transfer in catchment systems. Many studies highlight the interaction between sediment and water in defining landscape connectivity, but many efforts to quantify and/or simulate sediment connectivity rely on the topographic/structural controls on sediment erosion and delivery. More recent modeling efforts integrate functional connectivity with structural connectivity. Though the recent modeling development is encouraging, a comprehensive sediment connectivity framework that integrates geomorphic and hydrologic processes across spatiotemporal scales has not yet been accomplished. Such an effort requires understanding the hydrologic and geomorphic processes that control sediment source, storage, and transport at different spatiotemporal scales and across various geophysical conditions. We propose an integrated hydrologic and sediment connectivity conceptual model to broadly categorize dominant sediment and hydrologic processes and patterns relevant to understanding sediment flux dynamics. The conceptual model describes dominant hydrologic-sediment connectivity regimes through spatial-temporal feedback between hydrologic processes and geomorphic drivers. The conceptual model helps to navigate different spatial dimensions and time scales of connectivity with 1) broad categorization of the structural characteristics against 2) categorization of the functional characteristics and time-scale variation of sediment connectivity. We propose that in combining hydrologic and sediment connectivity into a single conceptual model, patterns emerge such that catchments will exist in a single characteristic behavior at a particular instance, which would shift with space and time, and with landscape. Using the conceptual model as a "thinking" tool, we extract case studies from a multidisciplinary literature review that correspond to each of the dominant hydrologic-sediment connectivity regimes. Sediment and water interactions in real-world examples are examined using various observational and modeling techniques. The conceptual model and case studies provide a foundation for advancing the understanding and predictive capability of watershed sediment processes at multiple spatiotemporal scales.